STUDY ON THE NON-LINEAR VIBRATION IN THE HYDRAULIC SCREW DOWN VERTICAL SYSTEM FOR ROLLING MILL - ZHANG RuiCheng; MA YinZhou; GAO Zheng; WEN JiaHe (Jixie qiangdu)
For vertical vibration systems tend to ignore the influence of hydraulic screw down system in the rolling mill,two degrees of freedom hydraulic screw down vertical vibration system model was established based on viscous damping between the hydraulic cylinder and the frame,nonlinear stiffness between the rolling interface. By means of a multiple scales method,the existence and stability of periodic solutions in a first order approximation close to the main parametric resonance were investigated,and the frequency-response equation was provided. The impacts of nonlinear stiffness and viscous damping on the rolling mill vibration were analyzed,and the impacts of excitation frequency on non-linear vertical vibration were analyzed by the phase plane method,the Poincare mapping method and the maximum Lyapunov exponent. Analysis’ s results provide a reference for engineering to solve the vibration problem of hydraulic screw down system.